Journal Metrics of Orthopaedic Journals between 2016 and 2021: Trends and Comparisons with Other Specialties - Cedeno, Edgar; Pasqualini, Ignacio; Emara, Ahmed K.; Ibaseta, Alvaro; Oyem, Precious C.; Deren, Matthew; Krebs, Viktor E.; Molloy, Robert; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2024)
Bibliometric analysis plays a crucial role in elucidating publication trends and aids scholars in gauging the reach of prospective journals for their research dissemination. Concerns with impact factor (IF) have led us to examine the trends in IF, corrected IF (cIF), and Citescore in orthopaedic journals from 2016 to 2021 and compare them with internal medicine and general surgery journals. Journal IF and cIF were obtained from Journal Citation Reports and Citescore data from the Elsevier Scopus database for the years 2016 to 2021. Orthopaedic journals were categorized, and 10 medicine and surgery journals were selected for comparison. Mean values were analyzed to identify trends. The study included 52 orthopaedic journals, evenly split between the United States and the rest of the world, predominantly publishing in English. Mean IF in orthopaedic journals increased from 1.93 (2016) to 2.78 (2021), with similar rises in cIF and Citescore. These trends were consistent in specialty and general orthopaedic journals. No significant differences were found in mean IF between these categories. Medicine and surgery journals also experienced significant IF increases. Orthopaedic journals have experienced growing esteem and extent from 2016 to 2021. Specialty and general orthopaedic journals showed parallel growth. Researchers can utilize this analysis for informed publishing decisions, potentially expanding their readership.
Keywords: bibliometric; impact factor; orthopaedic journals; Citescore; publication trends